Sunday
March 26, 2017

Post a New Question

Posted by on .

Show that both functions y1=e^(-2x) and y2=xe^(-2x) are solutions to the differential equation y^''+4y^'+4y=0

  • Calculus - ,

    what's the troub;e? Just plug and chug

    y1 = e^(-2x)
    y1' = -2e^(-2x)
    y1" = 4e^(-2x)

    y"+4y'+4 = 0

    y2 = xe^(-2x)
    y2' = (1-2x) e^(-2x)
    y2" = (4x-4) e^(-2x)

    y"+4y'+4y = 0

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question